Visualization of electron beam image - Boriskin, V.N.; Zakutin, V.V.; Reshetniak, N.G.; Romanovsky, S.K.; Tenishev, A.Eh.; Titov, V.J.; Chertishev, I.A.; Shevchenko, V.A.; Shlyakhov, I.N.; Uvarov, V.L. (Вопросы атомной науки и техники, 2014)
The system for visual monitoring of the electron beam was developed and implemented. The technique is based on registration of optical radiation, which is generated under object-beam interaction. The system comprises image transferring channel, remote-controlled digital photo-camera, connected with PC by USB-interface as well as proper software. The images obtained give information on the beam density distribution over the surface of the object being irradiated. 40 keV and 10 MeV electron beams were researched.